Keteladanan dalam Kitab Nadzom Syaikhina ‘Ala Hikayati Khadim Al-Ma’had Dar Al- ‘Ulum Banyuanyar Al-Islami Asy-Syekh Al-Haj Muhammad Syamsul Arifin Karya Muhsin Muis - Ukhrawiyah, Faizetul; Hadaniyah, Rusmawati; Umniyah, Umniyah (Dzil Majaz: Journal of Arabic Literature, 2024)
The book "Nadzam Syaikhona" is the first work that explores the life story of KH. Moh. Syamsul Arifin, the caretaker of Banyuanyar Islamic boarding school, from his childhood until his passing. This book employs the bahr rajz, making it suitable for analysis using a structuralism approach. The analysis utilizes a qualitative descriptive literature research method with the data collection technique of reading and note-taking. The research results present the story of KH. Moh. Syamsul Arifin. The characters include Syaikhona Moh. Syamsul Arifin, KH. Hamid Baqir, and Ny. Halimah Baqir. The background encompasses the time setting from Syaikhona's birth on June 6, 1945, to the time of his passing on July 1, 2021 CE. The settings include 1) Pakes, Panaan, Palengaan - Syaikhona's birthplace, 2) his grandmother's house where he hides to enjoy delicious food, 3) Bata-bata, 4) Alas Bulu, Wongsorejo, 5) Banyuwangi, 6) Sidogiri Islamic boarding school, 7) Banyuanyar Islamic boarding school, 8) Karang Suko, Malang, 9) Mecca, 10) Bangkalan, 11) Panji Siwalan, 12) Toronan, 13) Tamberu. The plot unfolds using a forward and backward sequence, and the perspective is from a third-person point of view. The literary style employs the bahr rajz with the wazan مستفعلن مستفعلن مستفعلن × مستفعلن مستفعلن مستفعلن and berqafiyah. The message contained is the guidance of Syaikhona to the students, teachers, and everyone regarding family matters, work principles, and how to respect the Quran.